Enfrentamiento entre naturaleza y cultura en el ensayo latinoamericano (Estudios) - Sacca, Zulma (2015)
There are very few texts about the essay as a genre or about the essay as a genre in Latin America. All the questions should be focused on how to think formally about this line of thought. A proposal for reflection, and for finding a definition and systematization may be found in the confrontation between nature and culture. As an instrument of analysis, this principle is too general and does not have an ending where the conflict can be solved. It wouldn’t be a very profitable reflective method in Latin America either, where this very conflict is surmounted and thought starts from a unique and exclusive blend of Nature and culture. Despite this, it might be an effective method of analysis as long as it considers the merging of the nineteenth-century discourses with the production of the twentieth century as its foundation. Latin American essay production has at its core its need to translate itself in historical events, to become the direction of history. Although there were differences in the degree and even drastic distinctions in the way that translation was conceived, all the essay writers started from a fundamental premise: to take the object of reflection in its own conditions and draw from them the principles to insert them in history.